The CSPOFL: Assessing College Students’ Perception of Flexible Learning Using the Multimodal Model of Online Education - Loseñara, Jleian Mard (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2024)
Online or flexible learning has increased drastically even before the sudden change in educational modalities related to COVID-19. This study aims to design and validate the student perception of flexible learning (CSPOFL) through an instrument based on the multimodal online education model, which consists of seven constructs. This applied research uses an instrument development design and validation design after testing the validity and reliability of eight content experts and 164 students at a state university. The data collection method uses a questionnaire. The data collection instrument was used with a questionnaire sheet. The data analysis technique uses quantitative and qualitative analysis. The results of the study are from 55 initial items; the final version of the instrument consists of 29 items. It was found that the modifications mentioned above in the constructs and items resulted in the consistency of the overall instrument reliability coefficient of 0.955, which implies the acceptability of the instrument for use. CSPOFL is recommended for teachers, schools, administrators, and policymakers who aim to assess how students perceive flexible learning so that necessary interventions can be formulated to improve the teaching and learning process.